the role of hyperlipidemia on nerve conduction - Al- Shareefi, shaymaa J.; El-Yassin, hedef D.; Dawoud, Abdul-Raheem H. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: previous reports suggested a connection between hyperlipidemia and neuropathy